Integrating Technology in Microteaching: Pre-Service EFL Teachers’ Digital Pedagogical Development - Yuvita Yuvita; Miasnikova Kseniia; Maria Yosephin Widarti Lestari (Universitas PGRI Semarang, 2026)
This study investigates the ways pre-service EFL teachers can achieve digital pedagogical competence through technology-integrated microteaching. Based on the increasing relevance of digital skills in teacher formation, this study aims to verify how microteaching enables technological integration and which factors condition this expansion. This study used a qualitative case study design with 23 pre-service EFL teachers at Universitas Pancasakti Tegal. Data were gathered through reflective journals, semi-structured interviews, classroom observations, videotaping and teaching documents and analysed with thematic analysis.The findings suggest a gradual development in participants' digital pedagogical awareness from merely using technology towards more pedagogically purposeful integrators. Also, technology use increased creativity in teaching and provided opportunities for building confidence through practice and reflection. Nonetheless, this development was affected by multiple elements such as technological hurdles, commentary from peers and lecturers, cooperative learning, and institutional assistance. The finding also shows the cognitive, emotional, social and contextual dimensions that shapes the digital pedagogical competences. It suggests that microteaching creates a productive space for reflective and experiential learning on the topic of technology integration, and that teacher education programs should create supportive environments to further develop pre-service teachers’ digital competence